2019
DOI: 10.1021/acs.jpclett.9b00088
|View full text |Cite
|
Sign up to set email alerts
|

Oxyhydride Nature of Rare-Earth-Based Photochromic Thin Films

Abstract: Thin films of rare-earth (RE)–oxygen–hydrogen compounds prepared by reactive magnetron sputtering show a unique color-neutral photochromic effect at ambient conditions. While their optical properties have been studied extensively, the understanding of the relationship between photochromism, chemical composition, and structure is limited. Here we establish a ternary RE–O–H composition-phase diagram based on chemical composition analysis by a combination of Rutherford backscattering and elastic recoil detection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
105
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(117 citation statements)
references
References 41 publications
12
105
0
Order By: Relevance
“…Clearly, in situ illumination studies using PALS may aid to reveal which type(s) of open volume defects in the YO x H y films are generated in an apparently irreversible way during a full photodarkening-bleaching cycle. The remarkable changes in the Doppler parameters during UV illumination may stem from either of the following possible causes, including (i) charging of positively charged vacancy levels by photo-excitation of valence band electrons V (+) + e − → V (o) , leading to the presence of positron-trapping neutral vacancies, (ii) the formation of hydrogen-rich metallic YH 2−δ or YO x H 3−2x (x > 0.5) clusters [7], perhaps caused by photo-induced local transport of H − and local phase segregation, (iii) changes in the formation of positronium due to the presence of photo-excited charge carriers in the photochromic state. Also, formation of vacancies by the UV illumination cannot be excluded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, in situ illumination studies using PALS may aid to reveal which type(s) of open volume defects in the YO x H y films are generated in an apparently irreversible way during a full photodarkening-bleaching cycle. The remarkable changes in the Doppler parameters during UV illumination may stem from either of the following possible causes, including (i) charging of positively charged vacancy levels by photo-excitation of valence band electrons V (+) + e − → V (o) , leading to the presence of positron-trapping neutral vacancies, (ii) the formation of hydrogen-rich metallic YH 2−δ or YO x H 3−2x (x > 0.5) clusters [7], perhaps caused by photo-induced local transport of H − and local phase segregation, (iii) changes in the formation of positronium due to the presence of photo-excited charge carriers in the photochromic state. Also, formation of vacancies by the UV illumination cannot be excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Under ambient conditions, photodarkened films reversibly bleach back thermally towards the initial transparent state when the UV excitation is removed, indicating that YO x H y and other rare-earth oxyhydrides are promising for application in smart windows [6]. A recent extensive study by Cornelius et al [7] reports on the detailed structural and compositional evolution of Y/YH x /YO x H 3−2x /Y 2 O 3 films upon varying the oxygen-to-hydrogen ratio in the Y-H-O ternary phase diagram [7]. Our previous study showed that the trends in the positron Doppler S-and W -parameter of Y/YH x /YO x H 3−2x /Y 2 O 3 thin films strongly correlate with the variation in their electronic structure, ranging from metallic and semiconducting nature to a widebandgap insulator with increased O:H ratio [8].…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] It has to be emphasized that the dual‐phase formation identified here clearly speaks against the notion of an oxyhydride nature of such photochromic thin films and charge neutrality arguments cannot be based on a formal metal valence of +3. [ 3,8 ]…”
Section: Implications For the Photochromic Mechanismmentioning
confidence: 99%
“…[ 8 ] This model was based on ion beam analysis and X‐ray diffraction data, obtained from photochromic oxygen‐containing scandium, yttrium, and gadolinium hydride thin films. [ 8 ] Recently, diffraction data from photochromic oxygen‐containing yttrium hydride were interpreted as indication for a multiphase nature. [ 9 ] Despite the fact that the phase formation has not been identified, [ 9 ] the interpretation of a multiphase nature is obviously in conflict with the notion of single‐phase photochromic metal oxyhydride thin films.…”
Section: Introductionmentioning
confidence: 99%
“…For their adequate handling in air, rare-earth hydride thin films are usually protected against oxidation by, for example, Pd capping layers [1]. However, the incorporation of oxygen in rare-earth hydrides after intentional exposure to air [2][3][4], or even through accidental contamination [5], leads to the formation of oxyhydrides, materials that contain oxide and negatively charged hydride [6][7][8][9], which exhibit very interesting properties. One of the pioneering works on this family of materials was carried out by Miniotas et al [5], who reported gigantic electrical resistivity in oxygen-containing gadolinium hydride.…”
Section: Introductionmentioning
confidence: 99%